’n Christelik-reformatoriese Evaluering van Neuro-linguïstiese Programmering as Psigo-terapeutiese Model - Vorster, C. M.; du Plooy, J. (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2005)
Before the development of the Neuro-linguistic Programming (NLP) model, there was a tendency to move away from scientific and rational thinking towards a belief in magic. This was later known as the New Age Movement. With the development of the New Age Movement various streams of thought mingled with one another and formed the foundation of the new way of thinking. The discussion of the basic streams of thought that have grown up and around the NLP model, serves as an introduction to a scientific-Christian critical-evaluation of the NLP model. Because of the very different points of view regarding the validity of the NLP model, it is necessary to consider the positive and the negative aspects of this model. From the point of view of a psycho-educationalist, an effort has been made to determine, through the critical analysis of this model, if it should be used with children in South Africa.